Highly efficient chiral resolution of DL-arginine by cocrystal formation followed by recrystallization under preferential-enrichment conditions - Iwama, Sekai; Kuyama, Kazunori; Mori, Yuko; Manoj, Kochunnoonny; Gonnade, Rajesh G.; Suzuki, Katsuaki; Hughes, Colan E.; Williams, P. Andrew; Harris, Kenneth D. M.; Veesler, Stephane; Takahashi, Hiroki; Tsue, Hirohito; et al. (Chemistry-A European Journal, 2014)
An excellent chiral symmetry-breaking spontaneous enantiomeric resolution phenomenon, denoted preferential enrichment, was observed on recrystallization of the 1:1 cocrystal of dl-arginine and fumaric acid, which is classified as a racemic compound crystal with a high eutectic ee value (>95%), under non-equilibrium crystallization conditions. On the basis of temperature-controlled video microscopy and in situ time-resolved solid-state (CNMR)-C-13 spectroscopic studies on the crystallization process, a new mechanism of phase transition that can induce preferential enrichment is proposed.
Keywords: Amino acids; chiral resolution; cocrystals; Crystal growth; phase transitions

Exploiting powder x-ray diffraction to establish the solvent-assisted solid-state supramolecular assembly of pillar[5]quinone - Shivakumar, Kilingaru I.; Yan, Yuncheng; Hughes, Colan E.; Apperley, David C.; Harris, Kenneth D. M.; Sanjayan, Gangadhar J. (Crystal Growth & Design, 2015)
We report the solvent-mediated supramolecular assembly of pillar[5]quinone (P[5]Q), a symmetric cyclamer containing five benzoquinone moieties bridged by five alternating methylene units. The supramolecular assembly of P[5]Q is shown to be facilitated by 1,1,2,2-tetrachloroethane (TCE) as solvent, producing a microcrystalline solvate material P[5]Q(.)2TCE with a fluffy texture. Optical and electron microscopy reveal that this material has a rod-shaped morphology, extending to several micrometers in length. Due to the microcrystalline nature of the material, structure determination was carried out directly from powder X-ray diffraction data, augmented by high-resolution solid-state C-13 NMR. The two crystallographically distinct TCE molecules occupy different types of void in the structure and have different dynamic properties. Crystallization of P[5]Q was attempted from a large number of different solvents, but only TCE was found to facilitate the formation of a crystalline phase. Indeed, features of the crystal structure suggest that the TCE component plays an important role in promoting the columnar assembly of P[5]Q molecules.